Detecting ball distribution patterns in table tennis by using autocorrelation method - Shioiri, A.; Ushiyama, Y.; Kamijima, K.; Sato, Y.; Ishida, H. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
The purpose of this research is to verify whether there is regularity in the player`s ball distribution pattern by collecting coordinate data of the ball fall position during the game. The coordinate data was measured by an analysis system of a ball distribution characteristic using an ultrasonic sensor. For the analysis of the distribution pattern, autocorrelation was used to verify the presence or absence of regularity. As a result, the rally and distribution patterns that showed a strong correlation were all negative. By autocorrelation analysis of coordinate data in the time series, it became clear that it is possible to judge whether there is regularity in rally or distribution pattern. By knowing regular rally and distribution patterns, it was thought that it might be a clue to judge the distribution tendency of the player or an effective distribution pattern or an invalid distribution pattern.